2015
DOI: 10.1186/s12948-015-0018-8
|View full text |Cite
|
Sign up to set email alerts
|

Perianal Crohn’s disease and hidradenitis suppurativa: a possible common immunological scenario

Abstract: BackgroundCrohn’s disease (CD) and Hidradenitis suppurativa (HS) are both chronic inflammatory diseases. The pathogenesis of these diseases is multifactorial, due to the interaction of genetic and environmental factors leading to a deregulated local immune response where T lymphocytes play a major role. To the best of our knowledge, no previous study has clarified whether the pathogenetic mechanism of perianal CD and HS is the same. We therefore analyzed the cellular expression pattern and the cytokine reperto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
(34 reference statements)
1
19
0
1
Order By: Relevance
“…14 Two recent studies reported a higher frequency of CD161+ CD4+ T lymphocytes in HS lesions. 15,16 Moran et al 16 demonstrated that the ratio of Th17 cells to CD4+ FoxP3+ CD127 low regulatory T cells (Tregs) in lesional skin was highly dysregulated in favour of IL-17 secreting Th17 cells. In lesional skin of patients with HS, increased levels of antimicrobial peptide LL-37 have recently been detected, which were associated with a Th1/ Th17 immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Two recent studies reported a higher frequency of CD161+ CD4+ T lymphocytes in HS lesions. 15,16 Moran et al 16 demonstrated that the ratio of Th17 cells to CD4+ FoxP3+ CD127 low regulatory T cells (Tregs) in lesional skin was highly dysregulated in favour of IL-17 secreting Th17 cells. In lesional skin of patients with HS, increased levels of antimicrobial peptide LL-37 have recently been detected, which were associated with a Th1/ Th17 immune response.…”
Section: Discussionmentioning
confidence: 99%
“…CD161 is a specific surface marker of Th17 cells, indicating their exclusive origin from a CD161+ CD4+ T‐cell progenitor . Two recent studies reported a higher frequency of CD161+ CD4+ T lymphocytes in HS lesions . Moran et al .…”
mentioning
confidence: 99%
“…CCR6 and RORc), in resting Th17 clones when compared to classic Th1. We and others already assessed that the frequencies of CD161+ Th17-derived Th1, Th17/Th1 and Th17/Th2, cells, positively correlated with severe phenotype of different chronic inflammatory disorders such as JIA, IBDs and asthma, respectively [3136]. In the same pathological conditions higher levels of CHI3L1 have been detected in patients’ serum respect to healthy donors [1416].…”
Section: Discussionmentioning
confidence: 99%
“…The Th17-derived Th1 cells expressed CD161, while the other Th1 cells present in the SF did not, and we named the former cells as non-classic, as compared with classic CD161− Th1 cells [33]. Moreover, we found an accumulation of Th17 and non-classic CD161+ Th1 lymphocytes in fistula curettage of patients suffering of fistulising Crohn’s disease [35, 36]. Another evidence of the high plasticity of human Th17 cells also emerges by the recent finding of the existence of a subset of human circulating memory CD4 T cells that produce both IL-17A and IL-4 [31].…”
Section: Introductionmentioning
confidence: 99%
“…59 The main differential diagnosis for HS is perianal fistulas associated with Crohn's disease: the two conditions may have overlapping imaging features, and at times may coexist. 57,60,63 Monnier et al showed that the fistulas in Crohn's disease are more complex and predominantly in the perianal region, with a slight increase in frequency of intersphincteric fistulas compared with HS. 58 In HS, the fistulas were more often bilateral and without associated rectal wall thickening.…”
Section: Hidradenitis Suppurativamentioning
confidence: 99%